ChemInform Abstract: From Minor Side Phases to Bulk Samples of Lanthanum Oxonitridosilicates: An Investigation with Microfocused Synchrotron Radiation. Issue 24 (27th May 2016) - Durach, Dajana; Schultz, Peter; Oeckler, Oliver; Schnick, Wolfgang
Abstract: Micrometer‐sized crystals of La11 Si13 N27.636 O1.046 :Ce 3+ are obtained as a side product from a mixture of La, La(NH2 )3, Si(NH)2, BaH2, and CeF3 (tungsten crucible, N2 atmosphere, 1650 °C, 5 h).